The Application Effect of PGPR Associated Bamboo Root and Rice Straw Compost on The Physical Quality for the Soil, Growth and Production of Corn Plants (Zea mays L) - Kurniasari, Indah; Budiyanto, Susilo; Lukiwati, Dwi Retno (Journal of Tropical Crop Science and Technology, 2021)
This research aims to examine the effect of application bamboo root PGPR and rice straw compost on the physical quality of the soil, growth and production of the corn plant (Zea mays). This research was arranged in split plot design 3 x 4 with 3 replications. The main plot is rice straw compost (K): K1=10 ton/ha, K2=15 ton/ha, K3=20 ton/ha. The subplot is PGPR (P): P0= 0 ml/l (control), P1=10 ml/l, P2=15 ml/l, P3=20 ml/l.  The parameters observed were soil porosity, soil water content, plant height, number of leaf, cob length, cob weight, weight of seed and field. Data were analyzed extensively and continued with Duncan Multiple Range Test (DMRT). The results showed that the treatment of PGPR and rice straw compost increases with the addition of dose. Treatment of PGPR provide a significant response to increase in the porosity, soil water content and number of leaf compared to the control, while the length of cob and weight of seed showed an increase in the addition treatment of a dose compost and PGPR. Treatment of PGPR or rice straw compost has yet to show a response different to the plant height. The interaction treatment significant on the weight of cob and field. The results of the optimal corn crop is achieved at the treatment dose of 15 ton/ha compost straw combined with PGPR dose of 15 ml/l.